Pemanfaatan Limbah Nikel Sorowako Dalam Campuran Stone Matrix Asphalt Kasar - Febe Priskila Supit; Robert Mangontan; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Industrial development in Indonesia is very rapid and has a good impact on the economy of a region or country. However, the negative impact that can be generated from the industrial output is waste in a very large amount and not used for an activity that is beneficial to an area. The purpose of this study was to conduct tests to determine the utilization of Sorowako nickel waste in coarse asphalt stone matrix mixtures by using a variation of asphalt content of 6.00%; 6.25%; 6.50%; 6.75% and 7.00% and tested the efficacy of the mixture against the duration of immersion, temperature, and water. The method used is to perform various examinations and specific tests regarding the aggregate and then design the structure of the coarse SMA mixture and also the marshall examination to obtain the characteristics of the mixture and the marshall immertion examination to obtain the residual Marshall stability value using the optimum bitumen content. From the results of this study, it is known that the material in the form of nickel waste meets the standard requirements of the General Bina Marga 2018, and can be used as a mixture of road pavement. The asphalt content used in the Marshall SMA rough test was 6.00%, 6.250%, 6.50%, 6.75%, 7.00%. The marshall immertion value with a KOA value is 7.00% and the remaining marshall stability value is 95.55% which has met the requirements of the 2018 Highways General Specification, which is 90%.